Physical and Sensory Quality of Sheep Meat Sate Grilled with Different Time and Fuel - Setiyono, Setiyono (2014)
The experiment was conducted to investigate the physical and sensory quality of sheep meat sate grilled with different time and fuel. Sheep meat was seasoned with spices and then grilled with three duration time (3, 5 and 7 minutes) and two kinds of fuel (gas and charcoal). The data observed were the physical quality of sheep meat sate (internal temperature, pH, tenderness, cooking loss and water holding capacity). Sensory quality included color, acceptability, texture, smell, taste and juiceness. The data of physical quality were statistically analyzed by variance analysis using completely randomized design 3x2 of factorial pattern (three kind of duration time of grilling and two kinds of fuel) and the differences between means were tested by Duncan’s New Multiple Range Test. The data of sensory characteristics were analyzed by analysis of non parametrik of Hedonik Kruskal- Wallis and then were analyzed by using Spider Web Design Test. The results showed that grilling time influenced significantly the internal temperature, cooking loss, and water holding capacity of sheep meat sate (P<0.01). Kind of fuel did not influence the internal temperature, tenderness, cooking loss and water holding capacity. There were no interaction between grilling time and kind of fuel on color (slightly black), acceptability (like), texture (smooth), smell (slightly burned) and taste (slighty delicious).